Conflicting premises in race relations: beyond resolution? / Qasim Ahmad - Ahmad, Qasim (Universiti Teknologi MARA, Shah Alam, 2004)
Needless to say, the issue of race relations in Malaysia can be viewed from a number of perspectives. K.J. Ratnam, analyzing the question (in pre Malaysia Malaya), for instance, opted for an approach that emphasized the communal factor. This factor, to him, supercedes the economic one in importance.1 Writing about two decades later, Hua Wu Yin finds this pluralist framework rather inadequate. While recognizing that ‘communal division in Malaysia society is a material reality’, Hua proceeds to place the issue in the context of a class analysis, seeing the state using communalism as a means to suppress working class interest.2 Collin E.R. Abraham also takes to combining the communal approach with that of the class analysis when dealing with the roots of race relations in colonial Malaya. He does this in order to overcome what he sees as the shortcoming of the pluralist concept which ‘is not so much analytical as descriptive’ and to, at the same time, avoid the ‘rigid two-dichotomy’ which would place ‘unnecessary limitations on an analysis of a socio-economic structure undergoing radical transformation under the impact of colonialism’3 No doubt the right diagnosis of the problem is crucial. Without the benefit of a precise identification of the real root of the malaise, one might argue, the appropriate handling of the entire issue might not be at all possible. However, critical though this particular aspect of the study is, this paper will not, regretfully, dwell further on it. Instead, it will focus on the place of the special position of the bumiputeras and how its consideration or reconsideration could have a bearing on the practice of race relations in Malaysia. In the course of the exercise, premises deemed to be held by the parties debating the issue would also be looked at. This is done so as to see whether or not they have any common meeting ground between them. On the other hand, should their premises clearly stand in direct conflict with each other, and then the question that perhaps needs to be raised is whether or not the conflict could somehow be resolved? If they are mutually exclusive, could it be that the conflict is in fact beyond resolution and what remains then